(untitled) (Research, Society and Development, 2021)
Electronic cigarettes were introduced to the market as a possible therapy for smoking cessation. However, e-cigarettes can contain several chemical substances, such as nicotine, in addition to heavy metals, such as iron and lead. This study aimed to analyze the use of electronic cigarettes in Brazil, through an integrative review. An integrative review was used with data search carried out in the Scielo, BVS and Academic Google databases, using the following descriptors: ’’use of electronic cigarettes’’ and ’’vaping’’, carried out from September to October 2021. It was observed that there are few studies carried out in Brazil on electronic cigarettes. It was found that electronic cigarettes are a big trend, especially among young males. It can be seen that the use of electronic cigarettes is related to the use of conventional cigarettes and other drugs. Furthermore, many individuals believe that e-cigarettes are not harmful to health or are less harmful than conventional cigarettes. The awareness of the population about the risks of using electronic cigarettes becomes essential in the educational process, aiming to alert the harm that these electronic devices can cause. Therefore, given the scarcity of scientific publications on the use of electronic cigarettes in Brazil, it is suggested that more studies be carried out that address the issue under discussion.